2003
DOI: 10.1021/ja0372412
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Performance of Methylalumoxane:  A Facile and Efficient Method to Trap “Free” Trimethylaluminum

Abstract: The presence of "free" trimethylaluminum (TMA) in methylalumoxane (MAO) solutions can be highly detrimental to the performance of metallocene and "post-metallocene" olefin polymerization catalysts. The most used strategy to remove "free" TMA is to evaporate MAO solutions to dryness, until a free-flowing white powder ("solid MAO") is left. This procedure is tedious and potentially hazardous, because in some cases the distillate is a concentrated hydrocarbon solution of TMA. Moreover, "solid MAO" is poorly solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
182
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(196 citation statements)
references
References 17 publications
10
182
1
3
Order By: Relevance
“…The results led us to conclude that in general propene insertion with 1,2 regiochemistry is dominant, for reasons that have been described (22). They also revealed that substituent R 2 , far from the active pocket, has virtually no effect on the catalytic behavior, whereas the steric bulk of R 1 , more to the catalyst front, is the key to control at the same time the enantioselectivity of 1,2 insertion and the propensity of the growing chain undergo ␤-H elimination to the monomer, which is by far the main chain transfer pathway in the absence of Al-trialkyls (17)(18)(19)23). It is important to note that the above is at odds with what is known for C 2 -symmetric ansa-metallocene cations, whose enantioselectivity and chain transfer properties are independently affected by different substituents (7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results led us to conclude that in general propene insertion with 1,2 regiochemistry is dominant, for reasons that have been described (22). They also revealed that substituent R 2 , far from the active pocket, has virtually no effect on the catalytic behavior, whereas the steric bulk of R 1 , more to the catalyst front, is the key to control at the same time the enantioselectivity of 1,2 insertion and the propensity of the growing chain undergo ␤-H elimination to the monomer, which is by far the main chain transfer pathway in the absence of Al-trialkyls (17)(18)(19)23). It is important to note that the above is at odds with what is known for C 2 -symmetric ansa-metallocene cations, whose enantioselectivity and chain transfer properties are independently affected by different substituents (7).…”
Section: Resultsmentioning
confidence: 99%
“…The experiments at lower propene concentration were carried out in a 250-ml magnetically stirred, two-necked, jacketed Pyrex reactor; those at higher concentration were carried out in a 2-liter magnetically stirred, stainlesssteel reactor (Brignole AU-2). In all cases, the precatalyst was dissolved in toluene and activated with methylalumoxane [Crompton (Middlebury, CT) 10% (wt͞wt) solution in toluene] added with 2,6-di-tert-butylphenol (Aldrich) to trap ''free'' trimethylaluminum (23). The general procedures can be found in Supporting Text.…”
Section: Methodsmentioning
confidence: 99%
“…We employed BHT as the modifying reagent of trialkylaluminum in MMAO reported by Busico [30]. The results are shown in Table 1.…”
Section: Copolymerization Of Propylene With ω-Alkenols and Higher 1-amentioning
confidence: 99%
“…Phenoxy-imine ligands in complexes contain alkyl substituents in the 2nd and the 4th positions of their phenyl rings, they produce moderately syndiospecific catalysts [55,56]. Detailed investigations of the Ti and Zr complexes with the same ligands showed a surprising difference in the chemistry of polymerization reactions.…”
Section: Polymerization Of Higher α-Olefin With Fi Catalystmentioning
confidence: 99%
“…The [rrrr] content in polypropylene produced with these complexes at 0-20 0 C can reach 0.95-0.96 corresponding to a very high probability of syndiotactic linking, ~0.99 [55][56][57][58]. However, a replacement of these substituents with two bromine or two iodin atoms changes the regiocontrol to primary and the stereocontrol to moderately isospecific, the [mm] values of polypropylene prepared at 0 0 C increases from 0.17 for dialkyl-substituted complexes to 0.73 for diiodo-substituted complexes [58].…”
Section: Polymerization Of Higher α-Olefin With Fi Catalystmentioning
confidence: 99%